Indoprofen prevents muscle wasting in aged mice through activation of PDK1/AKT pathway. Issue 4 (25th February 2020) - Kim, Hyebeen; Cho, Sung Chun; Jeong, Hyeon‐Ju; Lee, Hye‐Young; Jeong, Myong‐Ho; Pyun, Jung‐Hoon; Ryu, Dongryeol; Kim, MinSeok; Lee, Young‐Sam; Kim, Minseok S.; Park, Sang Chul; Lee, Yun‐Il; et al.
Abstract: Background: Muscle wasting, resulting from aging or pathological conditions, leads to reduced quality of life, increased morbidity, and increased mortality. Much research effort has been focused on the development of exercise mimetics to prevent muscle atrophy and weakness. In this study, we identified indoprofen from a screen for peroxisome proliferator‐activated receptor γ coactivator α (PGC‐1α) inducers and report its potential as a drug for muscle wasting. Methods: The effects of indoprofen treatment on dexamethasone‐induced atrophy in mice and in 3‐phosphoinositide‐dependent protein kinase‐1 (PDK1)‐deleted C2C12 myotubes were evaluated by immunoblotting to determine the expression levels of myosin heavy chain and anabolic‐related and oxidative metabolism‐related proteins. Young, old, and disuse‐induced muscle atrophic mice were administered indoprofen (2 mg/kg body weight) by gavage. Body weight, muscle weight, grip strength, isometric force, and muscle histology were assessed. The expression levels of muscle mass‐related and function‐related proteins were analysed by immunoblotting or immunostaining. Results: In young (3‐month‐old) and aged (22‐month‐old) mice, indoprofen treatment activated oxidative metabolism‐related enzymes and led to increased muscle mass. Mechanistic analysis using animal models and muscle cells revealed that indoprofen treatment induced the sequential activation of AKT/p70S6 kinase (S6K) and AMP‐activated protein kinase (AMPK), which in turn can augment protein synthesis and PGC‐1α induction, respectively. Structural prediction analysis identified PDK1 as a target of indoprofen and, indeed, short‐term treatment with indoprofen activated the PDK1/AKT/S6K pathway in muscle cells. Consistent with this finding, PDK1 inhibition abrogated indoprofen‐induced AKT/S6K activation and hypertrophic response. Conclusions: Our findings demonstrate the effects of indoprofen in boosting skeletal muscle mass through the sequential activation of PDK1/AKT/S6K and AMPK/PGC‐1α. Taken together, our results suggest that indoprofen represents a potential drug to prevent muscle wasting and weakness related to aging or muscle diseases.